Chemical association and mobility of trace elements in 13 different fuel incineration bottom ashes. (15th May 2016) - Saqib, Naeem; Bäckström, Mattias
Highlights: Bottom ashes from 13 Swedish waste incineration facilities were collected. Trace elements contents followed the sequence as Cu > Zn > Pb > Cr > Ni > Sb > As. Standard leaching indicates Cr had strongest mobility followed by Pb, Sb and Cu. Large amount of Cu is found in organic bound phase in 31% of samples. Amounts of unstable trace elements in biofuel bottom ashes are comparatively lower. Abstract: The release of trace elements from waste incineration bottom ash is problematic during utilization/landfilling. Thirteen bottom ashes (from various waste fuels and wooden/mixed wooden fuel) were investigated with respect to the total content, leaching behaviour by standard leaching procedure (EN 12457-3), and chemical association of trace elements by sequential extraction. Results showed that the content of trace elements in household/or industrial waste bottom ashes were of high level in comparison to in wooden/mixed wooden fuel/mixed wooden waste ashes. Type of fuel being treated greatly impacts the total inventory of trace elements. On average, trace element content in 13 ashes followed the decreasing order; Cu > Zn > Pb > Cr > Ni > Sb > As. In this study the average total content of Zn, Pb, Cu and Cr was higher in grate bottom ash treating household/industrial waste in comparison to fluidized boilers ash using same waste, however, there were too few data points and variation in data was large. By Standard leaching procedure, an excessive amount (more than disposal limit) of leached Cr, Pb, Sb and Cu (mostly in household/industrial waste ash) was observed in 6, 5, 5 and 4 of the 13 samples, respectively. Correlation coefficients ( r ) found between total and water leachable contents for Cu, Sb and As were 0.8, 0.7 and 0.6 respectively. Sequential extraction indicated that residual was the major fraction mostly, however, considerable amounts of trace elements had the potential to leach out. A large fraction of arsenic (57% based on average values) in 5 samples (mostly in waste/virgin wood and mixed wooden waste/fuel) and Zn (49% based on average values) in 4 of 13 samples (mostly household/or industrial) were found in the fractions that are easily available (acid soluble and exchangeable). Further, a considerable amount of Cu in 4 samples were found associated with the organic-bound phase. Dissolved organic matter might play an important role in leaching of Cu during utilization/landfilling. Moreover, principal component analysis (PCA) showed that fuel type affects the association of trace elements in bottom ash. Amounts of labile trace elements in wooden/mixed wooden fuel/waste bottom ashes were comparatively lower than other fuel bottom ashes. None of the samples exceeded the limit of disposal with respect to DOC leaching while chlorine in two and sulphate in three samples (household/industrial) exceeded limit. LOI (550 °C) values were higher for bottom ash from grate facilities probably due to no-pre-treatment of the waste fuel. While comparatively low values of LOI (1 000 °C) in few samples implies that the oxidation might have outweighed the loss of carbonates.